CLINICAL AND LABORATORY CHARACTERISTICS OF PERIRENAL ABSCESS CASES AND THEIR MANAGEMENT - Rizaldi, Aril; Soetojo, Soetojo (Medicina Biomedica Journal, 2023)
BACKGROUND: Perirenal abscess is a rare disease, often leading to morbidity and mortality due to delay in diagnosis and inadequate treatment. Cases of perirenal abscess in RSUD Soetomo often have been going on for a long time and are severe.AIM: The purpose of this study was to determine the characteristics of patients with perirenal abscess and their management.MATERIAL AND METHODS: This research is a descriptive retrospective study. Characteristics of patients with perirenal abscess both clinical, laboratory, and management obtained from medical records at RSUD dr. Soetomo Surabaya during the period 2011-2016 and analyzed using SPSS 20.0.RESULTS: There were 38 patients with perirenal abscess with the mean age was 46.21 11.74 years. Most of the abscesses were mixed (peri-pararenal) namely 21 patients (55.2%), 15 patients (39.5%) perirenal abscess and 2 patients (5.3%) pararenal abscess. The most risk factors for perirenal abscess were 17 patients (44.7%) with kidney/ureter stones and 15 patients (39.5%) with diabetes. The most frequent clinical symptoms were low back/abdominal pain in 38 patients (100%), mass in the waist/lower abdomen in 36 patients (94.7%) and fever in 28 patients (73.7%), CVA tenderness in 28 patients (73, 7%), and nausea/vomiting in 12 patients (31.6%). From the laboratory, 29 patients (76.3%) were anemic, 28 patients (73.7%) had hypoalbuminemia, and 32 patients (84.2%) had leukocytosis. Management in the form of abscess drainage, namely 35 patients (92.1%) underwent open drainage surgery, 3 patients (7.9%) underwent open drainage surgery and nephrectomy.CONCLUSION: Perirenal abscess has non-specific clinical signs and symptoms is sometimes difficult to make a diagnosis. Patients with low back/abdominal pain with a lump in the waist and fever lasting more than 5 days may suggest a perirenal abscess and need further diagnostics. Abscess drainage is the best option for the treatment of perirenal abscesses.